MicroRNAs with non-additive expression in the ovary of hybrid hens target genes enriched in key reproductive pathways that may influence heterosis for egg laying traits - Isa, Adamu Mani; Sun, Yanyan; Li, Yunlei; Wang, Yuanmei; Ni, Aixin; Yuan, Jingwei; Ma, Hui; Shi, Lei; Tesfay, Hailai Hagos; Fan, Jing; Wang, Panlin; Chen, Jilan (Frontiers in Genetics, 2022)
Heterosis has been extensively exploited in chicken breeding to improve laying traits in commercial hybrid stock. However, the molecular mechanisms underlying it remains elusive. This study characterizes the miRNAome in the pre-hierarchical follicles of purebred and hybrid laying hens, and investigate the functions of miRNAs with non-additive expression in the pre-hierarchical follicles as they modulate heterosis for egg number and clutch size. To achieve that aim, White Leghorn and Rhode Island Red chicken lines were reciprocally crossed to generate hybrids. The crossbreds demonstrated heterosis for egg number and clutch size, and pre-hierarchical follicles from 4 birds of each genotype were collected at 53 weeks of age. Mode of miRNA expression was characterized after miRNA sequencing. A total of 50 miRNAs including 30 novel ones, were found to exhibit non-additive expression. Dominance was the predominant mode of expression exhibited by majority of the miRNAs. Functional analysis of target genes of the known miRNAs with non-additive expression revealed GO terms related to regulation of transcription, metabolic processes and gene expression. KEGG and REACTOME pathways including hedgehog, cellular senescence, wnt, TGF-β, progesterone-mediated oocyte maturation, oocyte meiosis, GnRH signaling pathways, signal transduction and generic transcription, which can be linked to primordial follicle activation, growth and ovulation, were significantly enriched by target genes of miRNAs with non-additive expression. Majority of the genes enriched in these biological pathways were targeted by gga-miR-19a, gga-miR-19b, gga-miR-375, gga-miR-135a, and gga-miR-7 and 7b, thus, revealing their synergistic roles in enhancing processes that may influence heterosis for egg number and clutch size in hybrid hens.